Adjustment in Africa : Update on Reversing Economic Decline in Sub-Saharan Africa - Jones, Christine W. (World Bank, Washington, DC, 2012)
This study reviews the Bank's experience with adjustment lending to Sub-Saharan Africa (SSA), from FY80 to FY96. During this period, a total of 163 adjustment operations, for $15 billion have been approved to 37 countries. Of these, a total of 121 have already been evaluated at completion. The study is based on information from all the operations, both completed and ongoing. It focuses on the performance, outcomes, and impact at the country level. Performance is measured first in terms of compliance with conditionality in adjustment lending, and then an overall compliance rating is constructed for each country. The compliance rating is used to classify the countries into three groups: those with good, weak and poor compliance records. Design issues, most notably insufficient attention to borrower ownership, were already identified in the 1993 OED report on adjustment in SSA. The present study revisited and quantified the design issues identified in all of the 121 evaluations at completion. The detailed analysis of compliance with conditionality allows us to look at which types of policy reforms are more frequently included in adjustment operations, and which ones are more often complied with. The main recommendations emerging from the findings of this report are the need for: (i) increased selectivity in adjustment lending; (ii) improved design; and (iii) improved benchmarks and indicators of progress towards the goals of poverty alleviation and fiscal sustainability.